Inferences by Parallel Reasoning in Islamic Jurisprudence : Al-Shīrāzī's Insights into the Dialectical Constitution of Meaning and Knowledge /: Al-Shīrāzī's Insights into the Dialectical Constitution of Meaning and Knowledge. (2020) - Rahman, Shahid; Iqbal, Muhammad; Soufi, Youcef
No abstract available